If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(X) = (x + 4) + -2 Multiply f * X fX = (x + 4) + -2 Reorder the terms: fX = (4 + x) + -2 Remove parenthesis around (4 + x) fX = 4 + x + -2 Reorder the terms: fX = 4 + -2 + x Combine like terms: 4 + -2 = 2 fX = 2 + x Solving fX = 2 + x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'X'. f = 2X-1 + xX-1 Simplifying f = 2X-1 + xX-1
| 0.8x+.7=6.3 | | 0.8x+.07=6.3 | | 2.7=8.2+y | | 7/6c=3/5 | | p/-4=-63 | | -3/2m=7 | | y^3*3= | | y^2*3y= | | (8u^5+2u^2)/(-u^2) | | f(x)=(x-2)-4 | | 17+2x=21 | | h^2=705*207/34 | | 24x+3=5 | | 49/129=x/100 | | 8w+14=5w+6w-10 | | 60-2x=6x | | 7x=22+5x | | 90.00+20.00=70.00 | | 90.00+20x=30 | | 18.10x=42.25 | | n=50 | | 0=5t^2+20t+60 | | 26=-9x-2x-18 | | 2x+6/4x-8 | | 6=2w+41+3w | | 42=t+6 | | xsquared+7=9x | | (20x^3-27x^2-54x-16)/(5x+2) | | 9=3w+37+4w | | 1/2(t-5)=3 | | 9n+4=-5n-16 | | xsquared+x+3=0 |